NEW PYRENE DERIVATIVE - SAKON HIROTA; ADACHI CHIHAYA; NAGAI KAZUKIYO; OTA MASABUMI (1994)
PURPOSE:To provide the subject new derivative having excellent film-forming property and useful as a material for an organic electroluminescent element having luminescent function or electron-transfer function. CONSTITUTION:1,4-Di{2-(1-pyrenyl)vinyl}benzene of formula I. The derivative of formula I can be produced by the hydrogen reduction of a vinylene derivative of formula III obtained by the modified Wittig reaction shown in formula II.